(untitled) (Journal of the College of Basic Education, 2022)
The central goal of this study is to present the yes-no questions in transformational grammar. Furthermore, the study aims at contrasting the transformation of yes, no questions in English with their counterparts in standard Arabic in an attempt to clarify the areas of possible difficulties that may face Arabic learners in learning the formation of this kind of questions .